Dendritic Cells as Danger-Recognizing Biosensors - Seokmann Hong (Sensors, 2009)
Dendritic cells (DCs) are antigen presenting cells that are characterized by a potent capacity to initiate immune responses. DCs comprise several subsets with distinct phenotypes. After sensing any danger(s) to the host via their innate immune receptors such as Toll-like receptors, DCs become mature and subsequently present antigens to CD4+ T cells. Since DCs possess the intrinsic capacity to polarize CD4+ helper cells, it is critical to understand the immunological roles of DCs for clinical applications. Here, we review the different DC subsets, their danger-sensing receptors and immunological functions. Furthermore, the cytokine reporter mouse model for studying DC activation is introduced.